A study of code-switching amongst technical subject lecturers in a Malaysian Polytechnic / Mazlin Mohamed Mokhtar - Mohamed Mokhtar, Mazlin (2011)
The medium of instruction (MOI) has been an item that has been frequently discussed as the Malaysian Government changed the MOI of all the subjects in the Polytechnics from Bahasa Malaysia to English since 2008. This research looks at one of the ways that technical lecturers had tried to keep up with the change in the policy, which is code-switching between English and Bahasa Malaysia during lessons in order to enhance their teachings and also to accommodate with their proficiencies and the students' as well. This research will take a look at the frequency of code switching that technical lecturers used, the code-switching functions and the reasons for the technical lecturers code-switch in the teaching of Mathematics, Science or technical subjects. Both qualitative and quantitative methods of classroom observations, interviews and survey were carried out in one of the northern polytechnics in Malaysia, which is Politeknik Ungku Omar, Ipoh. The sample consists of three (3) technical lecturers and the students from the classes that they taught. The findings show that the lecturers used mostly of reiteration and message qualification functions when code-switching. They claimed that it was mainly to enhance their students' understanding and to save their time from lengthy explanation whenever the students are in doubt. This was agreeable by most students where they believe that code-switching could help them understand the lessons better. Some recommendations are made based on the findings from the classroom observations, interviews and survey in the hope that it would further improve the teaching of Mathematics, Science and technical subjects in the polytechnics in Malaysia.